2014
DOI: 10.1093/ije/dyu027
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Profile: Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: Chronic diseases are a global problem, yet information on their determinants is generally scant in low- and middle-income countries. The Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) aims to contribute relevant information regarding the development and progression of clinical and subclinical chronic diseases, particularly cardiovascular diseases and diabetes, in one such setting. At Visit 1, we enrolled 15 105 civil servants from predefined universities or research institutes. Baseline assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
451
4
70

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 511 publications
(538 citation statements)
references
References 14 publications
13
451
4
70
Order By: Relevance
“…The objective of ELSA‐Brasil is to determine the role of individual and environmental risk factors in predicting future CVD events and diabetes mellitus. The study design, methods, and recruitment of participants have been described previously 26. The study protocol was approved at all 6 centers of Brazil by their respective institutional review boards, and written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…The objective of ELSA‐Brasil is to determine the role of individual and environmental risk factors in predicting future CVD events and diabetes mellitus. The study design, methods, and recruitment of participants have been described previously 26. The study protocol was approved at all 6 centers of Brazil by their respective institutional review boards, and written informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information on the rationale and design of the ELSA‐Brasil study can be found in 2 previous publications 18, 19…”
Section: Methodsmentioning
confidence: 99%
“…All the participants signed a Free Informed Consent Term before the collection of clinical and laboratorial data. All international rules regarding data confidentiality in storage and analysis are being followed [7].…”
Section: Elsa-brasil Was Approved By the Research Ethicsmentioning
confidence: 99%